Я - женщина: стихи / Людмила Щипахина ; [художник В. Покусаев] - Щипахина Людмила Васильевна (Современник, 1984)
Экземпляры: Аб (1984) / Инвентарный номер: 6829 / Авт.знак: Щ 84 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Рус)6